Whither Multilateral Negotiation? China’s Foreign Policy in the South China Sea Dispute - Ramadhani, Eryan (Global and Policy Journal of International Relations, 2016)
ABSTRACTThis paper aims to examine the factors driving China’s rejection of multilateral negotiation to achieve dispute settlement in the South China Sea. China was a relatively closed country striving for internal stability during the leadership of Mao Zedong. The new era for China to engage the world came true after Deng Xiaoping made a history by opening up his country in the late 1970s. From that moment onward, China has been actively involved in varying cooperation both bilaterally and multilaterally. The partners with which China eagerly strengthens its relationship are the neighbors in Southeast Asia. Engagement with the Association of the Southeast Asian Nations (ASEAN) was one of China’s most fateful breaktrhough in the early 1990s, following the sanction imposed by the Western world due to the Tiananmen outbreak in 1989. China-ASEAN relationship has been thriving by leaps and bounds ever since. The South China Sea dispute putting China against Southeast Asian claimants, however, dims the good prospect of better relationship in the future. China’s assertive behavior in dealing with the dispute tarnishes the good image China has been portraying in the last two decades. Adding to such contradiction, China casts aside multilateral talks ASEAN members opt for. Instead, China compels the use of bilateral negotiation to be held between China and each claimant. This paper identifies three factors contributing to China’s preference of bilateral over multilateral negotiation: the apprehension about third party’s infiltration (i.e. the US), the concern over bargaining power, and the non-negotiable position in territorial sovereignty issue.Keywords: China, ASEAN, South China Sea dispute, multilateral negotiationDOI : https://doi.org/10.33005/jgp.v4i02.1909